Dietary zinc intake and zinc status differences between male and female elderls of South Jakarta community - Kusumaratna, Rina K.; Salim, Oktavianus Ch.; Sudharma, Novia I (Faculty of Medicine, Trisakti University, 2007)
IntroductionThe elderly have a greater risk of zinc deficiency compared to younger adults. This condition may be reflected by a lowered zinc intake and reduced zinc absorption in the elderly. The aim of the study was to explore the dietary zinc intake and zinc status differences between male and female elderly.MethodsA cross-sectional study was conducted included eighty-nine free-living subjects, aged above 60 years, apparently healthy and ambulatory. A two day and non consecutive diet record was used to assess energy and nutrient intake of the elderly. It was combined with a semi-quantitative food frequency questionnaire (SQ-FFQ), with food model that was also used to quantify the food pattern on each food frequency item. Serum zinc concentrations were measured by using atomic absorption spectrum photometry. ResultsThe total energy intake and normal serum zinc concentration in both genders of free-living elderly were mostly below the recommended dietary allowance. The mean serum zinc concentration did not differ significantly between female (13.7 Âµmo/l) and male elderly (13.9 Âµmo/l). Mostly the intake of zinc was below two thirds of the RDA it presented on intake of zinc in males was much less compared to female. Overall, the prevalence of zinc deficiency appeared low among the free-living elderly in South Jakarta.ConclusionsThe prevalence of zinc deficiency was relatively low in healthy elderly. Prevalence of zinc deficiency and zinc intake were lower in female compared to male elderly.